Erratum to Insight into particle production mechanisms via angular correlations of identified particles in pp collisions at √s=7 - Adam, Jaroslav; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Deisting, Alexander; Glässel, Peter; Kim, Jiyoung; Klewin, Sebastian; Knichel, Michael Linus; Leardini, Lucia; Mercado Pérez, Jorge; Oeschler, Helmut; et al. (The European physical journal. C, Particles and fields, 2019)
This document corrects two errors in Eur. Phys. J. C77 (2017) no. 8, 56: the incorrect referencing of Fig. 1 labels in three paragraphs in the results section and a missing acknowledgements section.
ALICE Collaboration: J. Adam, V. Anguelov, M. Arslandok, M.C. Danisch, A. Deisting, P. Glässel, J. Kim, S. Klewin, M.L. Knichel, L. Leardini, J. Mercado Pérez, H. Oeschler, A. Ohlson, Y. Pachmayer, F. Reidt, K. Reygers, R. Schicker, J. Stachel, J.H. Stiller, M.A. Völkl, D.F. Weiser, J. Wilkinson, B. Windelband, A. Zimmermann [und weitere]
Gesehen am 11.02.2020